Students’ Perceptions on the Use of Instagram in English Language Writing Activities - Nina’Imatul Farichah (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
Writing is one of the important skills for students in education. Rahmatunnisa (2014) mentioned there were some processes in writing which included the plan, draft, re-draft, edit, re-edit, re-plan, etc. However, in terms of a common issue, Indonesian students believe that writing is a difficult skill to learn. On the other hand the development of technology has resulted in the existence of social media. Instagram is one of social networking sites (SNS) that the students are familiar with. This research was conducted to explore the students’ perception on the use of Instagram in English writing activities and some factors that shape their perceptions; novelty, attitudes and experience. This research was descriptive qualitative research. It was conducted in one of the senior high schools in East Java. This school was chosen as the research area because based on my observation, all participants who participated in this study had participated in writing descriptive text activities on Instagram. Then, there were 4 students from 10th grade who participated in this research. Furthermore, I collected the data through interviews. Semi-structured interview was used in this research. For the interview, students were asked several questions related to their perception on the use of Instagram in writing activities and to analyze the data, I used Thematic Analysis which is guided by Braun and Clarke (2006). Based on the findings and discussion, the analysis revealed three themes: novelty, attitudes and experience. From the analysis, students showed a positive attitude on the use of Instagram in writing English and it could lead to positive perception as they perceived the learning process more positively. Experience also played a role in influencing students’ perception.
Reupload file repository 18 Mei 2026_Ratna ; FINALISASI oleh Agus 2026 Juni 17
Keywords: Writing